Nonprofit Organizations in Governance Arrangements: Adding Democratic Value to Community Reinvestment Act Agreements?. (2nd July 2016) - Casey, Colleen
Abstract : This article examines the democratic contribution of nonprofit organizations to governance arrangements. Conceptualizations of governance focus on the multisector arrangements between public, for-profit, and nonprofit organizations that emerge to create public value. Nonprofit organizations have been found to contribute efficiency and effectiveness to these arrangements; however, less is understood about the democratic contribution nonprofits make. It is hypothesized that nonprofits contribute democratic value when they pursue the public interest in accordance with their civil society function. A binary logistic regression analysis is performed on negotiated Community Reinvestment Act agreements from 2000 to 2009 to predict the types of nonprofits that participate in agreements. The results show that nonprofits involved in agreements represent the public interest, as measured by their organizational purpose, representation in communities of need, and organizational capacity. The article suggests that the public interest consequences of governance arrangements vary based on the sources of accountability introduced by the participating organizations.